Ôn tập chương Biểu thức đại số

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
PT Bích Ngọc

f (x) = -6x2+x3-8+12x

g (x) = x3-3x2+6x-8

a) Tính f (x) +g (x) và g (x)- f(x)

b) Tính g (-1)

c) Tìm x để g (x)-f (x)=0

Miinhhoa
17 tháng 4 2019 lúc 22:54

a, f (x) + g (x)

= \(-6x^2+x^3-8+12x+x^3-3x^2+6x-8\)

= \(-9x^2+2x^3-16+18x\)

g (x) - f (x)

= \(x^3-3x^2+6x-8+6x^2-x^3+8-12x\)

= \(3x^2-6x\)

b, Tính g (-1)

g (x) với x = (-1)

ta có : g (-1) = \((-1)^3-3.(-1)^2+6.(-1)-8\)

= \((-1)-3-6-8\)

= (-18)


Các câu hỏi tương tự
Lê Thảo Vy
Xem chi tiết
khanhhuyen6a5
Xem chi tiết
Hà Khánh Ly
Xem chi tiết
Vu Kim Ngan
Xem chi tiết
nguyễn thúy ngọc
Xem chi tiết
Huy Phan Đình
Xem chi tiết
Nhi Nguyen Phuong
Xem chi tiết
Nhi Nguyen Phuong
Xem chi tiết
Hoàng Ngọc Diệp
Xem chi tiết